Inflation risk and the cross section of stock returns - Fernando M. Duarte (Federal Reserve Bank of New York, 2013)
I establish that inflation risk is priced in the cross section of stock returns: Stocks that have low returns during inflationary times command a risk premium. I estimate a market price of inflation risk that is comparable in magnitude to the price of risk for the aggregate market. Inflation is therefore a key determinant of risk in the cross section of stocks. The inflation premium cannot be explained by either the Fama-French factors or industry effects. Instead, I argue the premium arises because high inflation lowers expectations of future real consumption growth. To formalize and test this hypothesis, I develop a consumption-based general equilibrium model. The model generates a price of inflation risk consistent with my empirical estimates, while simultaneously matching the joint dynamics of consumption and inflation, the aggregate equity premium, and the level and slope of the yield curve. My model suggests that the costs of inflation are significant: A representative agent would be willing to give up 1.5 percent of lifetime consumption to eliminate all inflation risk.
Keywords: E00; E31; E44; G00; 330; inflation; stock returns